2001
DOI: 10.2166/wqrj.2001.041
|View full text |Cite
|
Sign up to set email alerts
|

Application of Faecal Sterol Ratios in Sediments and Effluents as Source Tracers

Abstract: An analytical method to determine faecal sterols was developed and applied to the analysis of samples including pig manure, sewage treatment plant sludge and combined sewer overflow effluent. Compounds including coprostanol (5β-cholestan-3β-ol), epicoprostanol (5β-cholestan-3α-ol), cholesterol (cholestan-5-en-3β-ol) and dihydrocholesterol (cholestanol, 5α-cholestan-3β-ol) were quantified in these source samples and their relative ratios calculated to investigate their potential application as source tracers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…This list of sterol compounds is exhaustive and comparable to other studies in terms of number of sterols analyzed (Fernandez et al 2007;Leeming et al 1996;Nash et al 2005;Zhang et al 2008 Bull et al 2002;Fattore et al 1996;Chan et al 1998;Grimalt et al 1990;Carreira et al 2004;Froehner et al 2009;Marvin et al 2001;Patton and Reeves 1999 . Although the concentration of sterol compounds differed between influents and effluents, the order of abundance was basically the same.…”
Section: Gcms Methods For Sterol Detectionsupporting
confidence: 67%
See 1 more Smart Citation
“…This list of sterol compounds is exhaustive and comparable to other studies in terms of number of sterols analyzed (Fernandez et al 2007;Leeming et al 1996;Nash et al 2005;Zhang et al 2008 Bull et al 2002;Fattore et al 1996;Chan et al 1998;Grimalt et al 1990;Carreira et al 2004;Froehner et al 2009;Marvin et al 2001;Patton and Reeves 1999 . Although the concentration of sterol compounds differed between influents and effluents, the order of abundance was basically the same.…”
Section: Gcms Methods For Sterol Detectionsupporting
confidence: 67%
“…Studies that employ sterols and sterol ratios as markers for tracing anthropogenic pollution have typically employed as the sample matrix: sediments/ sludge (Carreira et al 2004;Fattore et al 1996;Froehner et al 2009;Marvin et al 2001;Mayer et al 2008), feces/manure (Jardé et al 2007a; Leeming et al 1996), or filter/residue from filtration of water samples (Devane et al 2006;Gilpin et al 2003;Grimalt et al 1990;Jardé et al 2007b). The present study applied sterol analysis to the result of direct liquid-liquid extraction of STP influents and effluents, which are complex matrices, in order to characterize sterol composition and calculate sterol ratios for comparison with literature-based sterol ratio values.…”
mentioning
confidence: 99%
“…Ergosterol is one of the precursors of vitamin D, while sitosterol, stigmasterol and campesterol are important constituents of higher plants (Weil, 1994). Previous studies have revealed considerable differences in both the content and the composition of fecal sterols of animals, and these variations have been related to diet differences (Walker, Wun, & Litsky, 1982;Leeming et al, 1996;Marvin, Coakley, Mayer, Brown, & Thiessen, 2001). Moreover, some anaerobic bacteria in the gut of warm-blooded animals are able to reduce sterols into stanols with isomeric configurations characteristic of each animal species.…”
Section: Steroids As Biomarkers Of Animal Fecesmentioning
confidence: 99%
“…The chromatographic techniques used here clearly resolved coprostanol and epicoprostanol based upon their different cis-and transstructures by lengthening the retention time. Once it had been established that there was not a significant amount of epicoprostanol in the sediments, coprostanol and epicoprostanol were considered together in ratios, following the precedent set by Venkatesan and Kaplan (1990), Sherwin et al (1993), Jeng et al (1996), Sherblom et al (1997), Chan et al (1998) and Marvin et al (2001). In particular, the authors showed that in ratios such as 5β/(5α+5β), the combination of coprostanol and epicoprostanol can elucidate the presence or absence of faecal material more clearly than on the basis of coprostanol alone.…”
Section: Resultsmentioning
confidence: 99%